THE RELATIONSHIP BETWEEN EMOTIONAL STABILITY AND THE LEVEL OF ACADEMIC STRESS IN NURSING PROFESSIONAL STUDENTS AT THE UNIVERSITY OF JAMBI DURING THE ADAPTATION OF NEW HABITS (AKB) - Lintang Athala; Retty Octi Syafrini; Riska Amalya Nasution (Program Studi Keperawatan Universitas Jambi, 2021)
Abstract Background: December 2019 a new virus Covid-19 was identified in the city of Wuhan. The Covid-19 Pandemic situation occurred for 2 years, showing improvements every day and also the vaccine target increasing and decreasing the level of PPKM, the Indonesian government implemented the Adaptation of New Habits (AKB) policies that had an impact on students on students' emotional stability and caused pressures on students. during learning so that academic stress arises which affects the learning process Methods: This type of research is quantitative (observational analytic) used a cross-sectional design with total sampling method. The number of samples used was 33 respondents. The study was conducted from January 28, 2022 to February 7, 2022. The data was collected using a questionnaire of emotional stability and academic stress. Results: The results of statistical tests used Correlation Gamma with p-value 0,001 < (0,05) obtained the results of a relationship between Emotional Stability and Academic Stress Levels in Nurse Profession Students at Jambi University During the New Normal. Conclusion: Based on the research, it shows that 55% are emotionally stable and 45% are emotionally unstable, with the dominant respondents being 58% of severe academic stress, 24% moderate, 15% very severe, 3% mild. This research can be considered to anticipate student academic stress, especially in self-management to reduce academic stress levels among students. Keywords: Academic Stress , Emotional Stability, New Normal. Abstrak Latar belakang: Desember 2019 virus baru Covid-19 diidentifikasi di kota Wuhan. Situasi Pandemi Covid-19 terjadi selama 2 tahun, menunjukan perbaikan setiap harinya dan juga target vaksin meningkatan dan penurunan level PPKM, Pemerintah indonesia memberlakukan Adaptasi Kebiasaan Baru (AKB) kebijakan yang berlakukan berdampak pada mahasiswa terhadap kestabilan emosi mahasiswa dan menyebabkan timbulnya tekanan-tekanan pada saat pembelajaran sehingga munculah stres akademik yang mempengaruhi proses pembelajaran. Metode: Jenis penelitian ini kuantitatif (analitik observasional) menggunakan design cross-sectional dengan metode pengambilan sampel Total sampling. Jumlah sampel yang digunakan 33 responden. Penelitian dilakukan pada 28 Januari 2022 hingga 7 Februari 2022. Pengumpulan data menggunakan kuesioner kestabilan emosi dan stres akademik. Hasil:. Hasil uji statistik menggunakan Correlation Gamma dengan p-value 0,001 < Î± (0,05) diperoleh hasil adanya hubungan Kestabilan Emosi Dengan Tingkat Stres Akademik Pada Mahasiswa Profesi Ners Universitas Jambi Di masa Adaptasi Kebiasaan Baru (AKB). Kesimpulan: Berdasarkan penelitian menunjukan 55% emosi stabil dan 45% emosi tidak stabil dengan dominan responden 58% stres akademik tingkat berat, 24% sedang, 15% sangat berat, 3% ringan. Penelitian ini dapat menjadi pertimbangan untuk mengantisipasi stres akademik mahasiswa, khususnya dalam penatalaksanaan mandiri untuk menurunkan tingkatan stres akademik dikalangan mahasiswa. Kata kunci: Adaptasi Kebiasaan Baru., Kestabilan Emosi, Stres Akademik,